Technological Process of Obtaining Sunflower Oil - Ioana Stanciu (Current Approaches in Engineering Research and Technology Vol. 9, 2024)
This chapter includes the main properties of olive oil, the types of sunflower from which the oil is extracted, as well as the technological scheme for obtaining refined sunflower oil. The nutritional function of sunflower oil is enhanced by the presence of provitamins A, D, and E, phosphatides as well as vitamins B4, B8, and K, they also contain sterol and tocopherols. Energy capacity: 8.8 cal/g oil. It is excellent for food because it has fluidity, color, taste and a pleasant smell. The technological process of obtaining sunflower oil includes the following main operations: reception of raw materials, storage of raw materials, cleaning of sunflower seeds, drying of oleaginous raw materials, peeling, grinding, frying, hydrothermal treatment and pressing, extraction with solvents and solvent recovery, refining of crude press oil and extractives, storage and packaging.